Perancangan chatbot berbasis Artificial Intelligence Markup Language (AIML) pada sistem informasi perpustakaan Senayan Library Management System (SLiMS) - Muhamad Abdurokhim; Syifaun Nafisah (FPPTI Jawa Tengah, 2023)
This research discusses the implementation of chatbot applications using Artificial Intelligence Markup Language (AIML) technology. The design of this application involves a chat interface that facilitates users to ask questions and get automatic responses based on pre-set knowledge. The discussion includes designing a chatbot application with use case diagrams and activity diagrams, using Natural language Processing (NLP) to process questions, verifying the data base for appropriate answers. As well as the development of an attractive user interface. The chatbot application is installed on the home page of the SLIMS library information system, to improve information accessibility and provide efficient interaction alternatives. Testing with Confusion Matrix shows the accuracy of Artivicial Intelligence markup language (AIML), The results show that the chatbot application can provide responses that match the pre-designed knowledge. This study has a positive impact in improving the ease of access to library information and it is important to continue to develop the chatbot knowledge to keep it relevant and effective. Thus, this chatbot application has the potential to support users in obtaining accurate information in the library. Keywords: Artificial Intelligence, Artificial Intelligence Markup Language, Chatbot